Bioremediation mechanism and potential of copper by actively growing fungus Trichoderma lixii CR700 isolated from electroplating wastewater. (1st January 2021) - Kumar, Vinay; Dwivedi, S.K.
Abstract: Present study investigated the Cu 2+ removal potential of Trichoderma lixii CR700, isolated from enormously heavy metal polluted electroplating wastewater. In the batch study, actively growing CR700 was able to remove 84.6% of Cu 2+ at the concentration 10 mg/L of Cu 2+ within 120 h after incubation and the accumulated and surface adsorbed amount of Cu was 0.51 and 0.47 mg/g of dry biomass respectively. T. lixii CR700 also showed efficient Cu 2+ removal potential in the pH ranges from 5.0 to 8.0, in the presence of other co-occurring contaminant such as heavy metal, anions and metabolic inhibitor as well from real tannery wastewater. Alteration on cell surface of Cu 2+ treated mycelia of T. lixii CR700 was analyzed using scanning electron microscope. Fourier transform infrared spectroscopic analysis was performed to identify the role of surface functional group in Cu 2+ adsorption which revealed that COO ─ functional group lead Cu 2+ adsorption onto the surface of T. lixii CR700. Thus, T. lixii CR700 uses simultaneous surface sorption and accumulation mechanism in Cu 2+ removal and can be potentially applied for bioremediation of Cu 2+ contaminated wastewater in ecofriendly, safe and sustainable way. Graphical abstract: Image 1 Highlights: T. lixii CR700 has high removal potential for Copper. T. lixii CR700 uses surface sorption and accumulation mechanisms for Cu removal. Surface sorption of Cu 2+ on mycelia surface of CR700 was happened via electrostatic attraction by COO ─ functional group. T. lixii CR700 has high bioremediation of Cu 2+ contaminated wastewater.